Analysis Of Factors Influencing Students Learning Motivation In Economic Subjects: (Survey Of Class XI IPS Students at SMAN 1 Karangnunggal Academic Year 2022/2023) - Esa Nurjanah; Heti Suherti; Ati Sadiah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The problem in this study aims to find out how the ideals or aspirations, learning ability factors, student condition factors, environmental conditions factors, dynamic elements factors in learning and the teacher's efforts to teach students influence the learning motivation of students in economics subjects. The population of this study were students of class XI IPS SMAN 1 Karangnunggal for the academic year 2022/2023 with a total of 144 students. The research sample used a saturated sample. In the Validity test using Pearson Correlation and Reliability test using Cronbach Alpha. The data analysis technique used is descriptive percentage analysis and factor analysis using confirmatory factor analysis. Based on the results of this study, namely the ideals or aspirations factor with a percentage value of 59,0% and eigenvalues of 3.968 and the variance is 9.679%, the learning ability factor is with a percentage value of 44,4% and the eigenvalues are 2.497 and the variance is 6.090, the factor student conditions with a percentage value of 38,9% and eigenvalues of 1.161 and a variance of 2.830%, environmental condition factors with a percentage value of 42,4% and eigenvalues of 1.659 and a variance of 4.047%, factors of dynamic elements in learning with values the percentage is 51,4% and the eigenvalues are 3.164 and the variance is 7.718%, the teacher's effort to teach students is with a percentage value of 59,7% and the eigenvalues are 16.966 and the variance is 41.381%.